489 The impact of education on novel concepts in adjuvant melanoma: a closer look at high risk stage II disease. (9th November 2020) - Parikh, Kinjal; Warren, Charlotte; Laar, Emily Van; Luke, Jason
Abstract : Background: Adjuvant therapy for patients with melanoma is currently recommended for patients with stage III disease with either immune checkpint inhibitors or combination dabrafenib/trametinib based on BRAF-status. Adjuvant treatment demonstrates improvement in recurence-free survival and overall survival. However, risk models suggesting that patients with stage IIB/IIC disease may have a higher risk of recurrence than patients with stage IIIA disease have prompted exploration into the use of adjuvant therapy in this patient subgroup as well. With several ongoing trials due to report, oncologists need education to stay up-to-date on the available data and contextualize this potential treatment option to implement therapy at the earliest point of clinical benefit to patients while also collaborating with surgical teams for optimal care planning. Methods: An online continuing education (CME) activity consisted of a multi-media 30-minute video panel of a medical oncologist and surgical oncologist discussing the rationale, available clinical trial data, and future directions of adjuvant therapy for the treatment of patients with stage II melanoma. 1 Educational effect was assessed using a repeated paired pre-assessment/post-assessment study design and compared the pre- and post-assessment responses. A chi-square test was used to identify differences between pre- and post-assessment responses. Effect size was calculated using Cramer's V test by determining the strength of the association between the activity and the outcomes (V = 0.16–0.26 is considerable and V > 0.26 is extensive). P values were calculated and those < 0.05 were considered statistically significant. Data from 65 oncologists and 138 surgeons are represented here through 8/12/2020. Results: Participation in education resulted noticeable educational effects for both oncologists (p < 0.01, V=0.143) and surgeons (p = 0.001, V=0.114): Statistically significant improvements in knowledge and competence were also seen regarding: -Knowledge regarding the rationale for adjuvant therapy in stage II diseaseo Oncologists: 46% pre; 69% post, p < 0.01o Surgeons: 24% pre; 36% post, p < 0.05 -Competence utilizing patient and tumor characteristics to identify potential candidates for adjuvant therapy in stage II diseaseo Oncologists: 52% pre; 77% post, p < 0.01o Surgeons: 29% pre; 43% post, p < 0.05-Increase in confidence was also observed for coordinating with the multidisciplinary team to augment surgical care with potential systemic adjuvant treatment for eligible patientso 22% improvement for oncologists o 19% improvement for surgeons Conclusions: This online, interactive, multi-media, expert-led, CME-certified educational activity resulted in significant gains in oncologist and surgeon knowledge and competence with improvements in confidence regarding the role of adjuvant therapy in the management of high risk stage II melanoma and recommending clinical trials for eligible patients. These results demonstrate the effectiveness of education, especially in online and on-demand formats and those requiring cross-discipline collaboration, and also highlights an ongoing need to further educate on this topic. Acknowledgements: This educational initiative was supported through independent educational grants from Bristol Myers Squibb. Reference: Luke J, Yoon C. Adjuvant Melanoma Treatment: Can We Improve Outcomes for More Patients: https://www.medscape.org/viewarticle/932047.